Calculation of Mass Attenuation Coefficients of Composite Tin Cans Using XCOM: A Computer Simulation Study - Auxtero, Eulogio, Jr.; Lazarte, Jessa Mae; Albero , Genaro (International Journal of Membrane Science and Technology, 2023)
Radiation shielding capability of a material depends on the parameters such as mean-free path (mfp), half value layer (HVL), and tenth value layer (TVL) which can be derived from the mass attenuation coefficients () of the materials. Measurement of the mass attenuation coefficients () of tin cans and tin can alloys is important for gamma-ray shielding. Steel can, Aluminum can and the alloy of the two at concentrations of 50%-50%, 67%-33%, 33%-67% were fabricated and their weight fractions were measured. The mass attenuation coefficients at an energy range of 1 keV-100 GeV for the prepared samples were evaluated. The mean-free path (mfp), half value layer (HVL), and tenth value layer (TVL) of the Tin can were evaluated using XCOM application at an energy of 1 MeV. Result indicates that lead and steel can have the lowest values of mfp, HVL, and TVL which implies that Steel can, like lead can be used as shielding for gamma rays. In addition, the trend of mass attenuation coefficients varies accordingly to the atomic numbers of elements with higher weight fraction in every sample. Further, Steel can which contains of mostly iron has the highest values compared to the Aluminum can. Finally, the results are compared to lead (Pb) which is a standard material for radiation shielding. This study shows promising result cost wise and in shielding capability.